2022
DOI: 10.1007/s00246-022-02927-8
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Magnetic Resonance in Children with Multisystem Inflammatory Syndrome in Children (MIS-C) Associated with COVID-19: Institutional Protocol-Based Medium-Term Follow-up Study

Abstract: Multisystem inflammatory syndrome in children (MIS-C) secondary to COVID-19 infection in previously healthy children often results in subtle but persistent echocardiographic abnormalities despite complete clinical recovery. This study was done to investigate medium-term cardiovascular outcomes of patients with MIS-C using cardiovascular magnetic resonance imaging (CMR). This is a single-center retrospective study of patients aged less than 21 years, diagnosed with MIS-C who received an outpatient CMR, around 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…With evidence of persistent diastolic dysfunction in a subgroup of patients up to 6-months, and suspicion of ongoing subclinical damage or previous scarring, CMR is an additional armament to help distinguish between these two processes and potentially provides novel insights into prognosis and pathophysiology. Since our last publication on mid-term CMR results from the same cohort, CMR was available in 3 more patients (25) (24,44,45). Myocardial edema on T2 weighted image was reported by Barris et.al in 44%, the reason for this large number of patients having persistent abnormal T2 weighted signal ratio, long after initial insult is unclear (44).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With evidence of persistent diastolic dysfunction in a subgroup of patients up to 6-months, and suspicion of ongoing subclinical damage or previous scarring, CMR is an additional armament to help distinguish between these two processes and potentially provides novel insights into prognosis and pathophysiology. Since our last publication on mid-term CMR results from the same cohort, CMR was available in 3 more patients (25) (24,44,45). Myocardial edema on T2 weighted image was reported by Barris et.al in 44%, the reason for this large number of patients having persistent abnormal T2 weighted signal ratio, long after initial insult is unclear (44).…”
Section: Discussionmentioning
confidence: 99%
“…Limited, single center studies have described almost complete resolution of ventricular systolic dysfunction and coronary artery changes within 3-6 months following discharge (15,(19)(20)(21). However, there is some evidence that subtle abnormalities in diastolic function on TTE and evidence of myocardial injury on cardiovascular magnetic resonance imaging (CMR) may persist longer (19)(20)(21)(22)(23)(24)(25). We have previously described the CMR results in a subset of patients at 6-month follow-up who had initial presentation with signi cant troponin leak and/or left ventricular systolic dysfunction (25).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…from the hospital showed no evidence of edema in T2-weighed sequences, and three patients had LGE [84]. Figure 9 describes CMR findings of elevated T1 relaxation time but no LGE in an 8-year-old girl three months after MIS-C.…”
Section: Cmr In Myocarditis With Mis-cmentioning
confidence: 96%
“…Other studies have shown diffuse myocardial edema on T2 inversion recovery sequences and native T1 mapping with no evidence of LGE one week after onset of symptoms, suggesting that CMR parametric mapping helps diagnose acute myocarditis in MIS-C in children [ 83 ]. On the other hand, another study in children where CMR was performed on 21 MIS-C patients six months after discharge from the hospital showed no evidence of edema in T2-weighed sequences, and three patients had LGE [ 84 ]. Figure 9 describes CMR findings of elevated T1 relaxation time but no LGE in an 8-year-old girl three months after MIS-C.…”
Section: Cmr In Myocarditis With Mis-cmentioning
confidence: 99%